The European Union's Trade Policies and their Economic Effects - Hoeller, Peter (OECD Economics Department Working Papers, 1998)
This paper retraces the Communities external liberalisation efforts, and discusses, where relevant, the repercussions of internal liberalisation on foreign competitors. The aim of the paper is to clarify, and when feasible, to quantify the economic effects of the EU's trade policies. To this end, it provides an overview of past liberalisation efforts, reviews trade indicators in international comparison and lays out the future trade agenda of the Community. The empirical evidence provided in the paper points to little evidence for trade diversion due to integration in Europe, while trade is likely to have boosted area-wide income significantly. It is openness in general, rather than regional integration, that has favoured growth in Europe ...